EU water directives through a semiotic lens: framing quality, risk, and circularity - Cordeiro, Cheryl Marie (Frontiers in Environmental Science, 2025)
European Union (EU) water governance operates through structured regulatory discourse that constructs meanings around water quality, risk, and circularity. These semiotic framings shape how environmental law is implemented, how compliance is defined, and how sustainability transitions are managed. This study applies a triadic semiotic framework of Greimassian semiotics, Social Semiotics, and Ecosemiotics, to analyze 11 foundational EU water directives. Using legal text analysis supported by AntConc software, the study deconstructs how regulatory language encodes categories, assigns agency, and positions ecological processes. The analysis reveals that water quality is primarily framed through rigid binary classifications such as compliant versus non-compliant, while risk is spatialized through threshold-based mapping and delineations of responsibility. Circularity is positioned mainly as an industrial-efficiency paradigm rather than an ecologically embedded process. These framings provide legal clarity and facilitate enforcement, but they also limit flexibility and reduce alignment with ecosystem dynamics. Social semiotic patterns show a consistent privileging of state and industrial actors, often marginalizing local communities and multispecies perspectives. Ecosemiotic analysis suggests that governance models rarely reflect the adaptive and fluid nature of aquatic systems. As a result, regulatory language may hinder ecosystem-based and transboundary approaches to water management. This research demonstrates that semiotic structures play a central role in shaping how environmental governance is operationalized. It argues for increased semiotic flexibility in legal design to better accommodate ecological complexity, institutional diversity, and climate variability. By advancing an interdisciplinary method that links semiotic theory with regulatory studies, this work offers new insights into how legal discourse mediates environmental outcomes in the EU context.